A new active balancing device utilizing rotating piezo actuators. (1st December 2022) - Jungblut, Jens; Haas, Julia; Rinderknecht, Stephan
Abstract: A new design for an active piezoelectric bearing with rotating actuators is presented and experimentally investigated in this paper. First, the theory of an active bearing with rotating actuators is presented. Afterwards, a model-free control approach based on the transform domain least mean squares algorithm is presented. The required transformation is extended by an efficient algorithm to compensate its delay. The mechanical and electrical design of the new device with three rotating actuators is presented afterwards. Experiments on a rotor test-rig are used to validate the functionality of the bearing with a feedforward control and passive rotor run-ups. The run-ups reveal vibrations of the third rotor order. A simple model comprising a hysteresis is presented to give a possible explanation for this phenomenon which shows that the order corresponds to the number of used actuators. A run-up on the test-rig with a prototype comprising five actuators shows strong vibrations of the fifth order. The paper closes with a thorough discussion on the feasibility of the new device as an active balancing device which includes a comparison to already existing devices.